Kožne in spolne bolezni - Trčko, Katarina (2019)
Skin Diseases and Sexually transmitted Infections. The content of the textbook is intended for the professional study program Zdravstvena nega and covers the wider field of dermatovenerology. The primary task of the skin is to protect us and transmit the stimuli from the outside world. This is facilitated by a specific structure and physiology, which are explicitly described in the textbook. The book presents important and common skin diseases and sexually transmitted infections, which the health worker most often encounters in daily work. The purpose of the textbook is to present to the reader the function of the skin as the largest organ, to teach the reader to recognize the conditions on the skin and to distinguish the changes and diseases of the skin and its appendages that need medical treatment. Information on rare skin diseases, such as various hereditary diseases, tropical dermatoses and systemic connective diseases, can be found in the additional literature listed at the end of the textbook.
Keywords: skin diseases; sexually transmitted infections; dermatology; skin; treatment of skin diseases